2008
DOI: 10.1111/j.1742-481x.2007.00347.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 concentrations in wound fluids rather than serological markers are useful in assessing bacterial triggers of ulcer inflammation

Abstract: Bacterial pathogenicity, microbial load and diversity are decisive for outcome and therapy of non healing ulcers. However, until now, no routine laboratory parameter is available to assess the inflammatory level caused by chronic wound infections. We thus investigated the usefulness of levels of interleukin (IL)-6 and tumour necrosis factor alpha (TNFalpha) in wound fluids for assessing ulcer inflammation in the presence or absence of microbial triggers. In addition, the predictive values of local cytokine ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 27 publications
1
40
0
Order By: Relevance
“…Nevertheless, in neuropathic diabetic foot ulcers the healing rate was also found to be inversely correlated with high bacterial loads (Xu et al 2007). Furthermore, in a study by Ambrosch et al, a good correlation between local CRP and TNF levels in wound washouts and tissue punch biopsies could be shown (Ambrosch et al 2008). …”
Section: Infection In the Diabetic Footmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, in neuropathic diabetic foot ulcers the healing rate was also found to be inversely correlated with high bacterial loads (Xu et al 2007). Furthermore, in a study by Ambrosch et al, a good correlation between local CRP and TNF levels in wound washouts and tissue punch biopsies could be shown (Ambrosch et al 2008). …”
Section: Infection In the Diabetic Footmentioning
confidence: 99%
“…The analysis of local IL-6 and TNF was shown to be able to discriminate between monomicrobial and polymicrobial infections in contrast to serum CRP and liposaccharide binding protein (LBP). Furthermore, local IL-6 was reported to reflect higher bacterial loads and infection, especially with pseudomonas (Ambrosch et al 2008). The determination of CRP as well as LBP as serological parameters, together with the semi-quantitative analysis of bacterial load and microbial identification, was performed.…”
Section: Infection In the Diabetic Footmentioning
confidence: 99%
See 1 more Smart Citation
“…These data suggested that the initiation of healing was not followed by a significant change in the level of bioactive TNF-a, and that the level of TNF-a may not be the main regulator of healing in chronic venous ulcers. Ambrosch et al (2008) showed that venous ulcers with mixed bacterial infection had increased TNF-a levels compared with monomicrobial infection, suggesting that elevation of TNF-a may also correlate with severity of infection.…”
Section: Cytokines/growth Factorsmentioning
confidence: 96%
“…Despite the pilot design, this work opens new perspectives for the study of foot infections at the molecular level, which is becoming an evolving field. [14][15][16] Equally interesting is the role of MRSA genetic factors in foot infection with this pathogen. 17 Wang et al 18 have examined risk and genetic factors in 429 patients hospitalized with diabetic foot infection.…”
mentioning
confidence: 99%